Grass-livestock interaction: a critical review of current research progress - Zhu, Xiaoyu; Tan, Dongfei; Li, Yutong; Shao, Changliang; Yan, Ruirui; Zhou, Wenneng; Xin, Xiaoping (Frontiers in Sustainable Food Systems, 2024)
Introduction Grass-livestock interaction is of great value in maintaining ecological balance, regional economic development, and the sustainability of grassland husbandry, which has gained attention in recent years in both academia and practice, however, study on grass-livestock interaction possesses cognitive bias and gaps. Methods This study clarified the latest research progress and development trend in the grass-livestock interaction field by illuminating publication trend, cooperative network, keyword co-occurrence relationship, keyword clustering during 2000 to 2022 based on the Web of Science core database. Results The results indicated that the annual number of publications in the grass-livestock interaction field showed a globally increasing with interdisciplinary and international collaboration, and the United States of America ranked firstly, followed by Brazil, England, Australia, China. Agricultural Research Service, the U.S. Department of Agricultures was the organization with the highest number of publications, and Rangeland Ecology & Management, Agriculture, Ecosystems & Environment, Grass and Forage Science were the top three journals. Furthermore, in terms of the temporal evolution, the research targeting the grass-livestock interaction mainly went through three stages: initial exploration period (2000–2011), to the period of rapid development (2012–2016) to transitional development period (2017–2022), and the notable existing keywords was Management, Livestock, Cattle, Vegetation, Growth, Soil. In terms of the structural composition, four broad divisions including mechanism of human activities, grassland resource monitoring and management, grassland livestock competition/adaptability, grassland land/soil research were identified. The results provide positive and objective insights into that grassland sustainability and grazing control through strengthening cross-disciplinary and cross-regional cooperation, and applying of standard methods based on evaluation system in the grass-livestock interaction field. Discussion The overall contribution of the work is provision of novel insight into the intellectual structure and temporal progression of grass-livestock interaction research at a macroscopic scale and the directions in which the field is headed currently.